2002
DOI: 10.1006/viro.2002.1618
|View full text |Cite
|
Sign up to set email alerts
|

B-Oligomer of Pertussis Toxin Inhibits HIV-1 LTR-Driven Transcription through Suppression of NF-κB p65 Subunit Activity

Abstract: The binding subunit of pertussis toxin (PTX-B) has been shown recently to inhibit the entry and postentry events in HIV-1 replication in primary T lymphocytes and monocyte-derived macrophages. While the effect of PTX-B on HIV-1 entry was shown to involve CCR5 desensitization, the mechanism of postentry inhibition remained unclear. In T lymphocytes, PTX-B affected transcription or stability of Tat-stimulated HIV-1 mRNAs. In this study, we sought to identify the mechanism of postentry inhibition of HIV-1 replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Also, it interferes with post-entry events in the HIV life cycle [20,22]. In this regard, its anti-HIV effect has been linked to inhibition of NF-kB activation [23]. Interestingly, NF-kB has been involved in extracellular Tat-induced signaling [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it interferes with post-entry events in the HIV life cycle [20,22]. In this regard, its anti-HIV effect has been linked to inhibition of NF-kB activation [23]. Interestingly, NF-kB has been involved in extracellular Tat-induced signaling [37].…”
Section: Discussionmentioning
confidence: 99%
“…PTX-B inhibits entry of R5-dependent HIV-1 in T cells and macrophages and post-entry steps of both R5-and X4-dependent HIV-1 life cycle in primary T cells [20,21], monocyte-derived macrophages (MDM) [22], as well as viral expression in chronically infected MDM [21,22] and cytokine-stimulated U1 cells [22,23]. PTX-B also inhibits Tat-driven transactivation in T lymphoid Jurkat cells [21], and stimulates anti-HIV specific cytotoxic T lymphocyte responses [24].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to those chemical inhibitors, the natural products mesalamine, mesuol and pertussis toxin appear to specifically block RelA phosphorylation, which is required for optimal RelA-mediated transactivation (Egan et al, 1999;Iordanskiy et al, 2002: Marquez et al, 2005. Moreover, the antiapoptosis protein Bcl-2 was shown to specifically inhibit transactivation by RelA in one study (Grimm et al, 1996), and antithrombin was reported to inhibit NF-kB transactivation by interfering with RelA-CREB co-activator interaction (Uchiba et al, 2004).…”
Section: Inhibitors Of Nf-kb Transactivationmentioning
confidence: 93%
“…Furthermore, Iordanskiy et al (2002) showed inhibition of NF-B by B-oligomer subunit of pertussis toxin in U-937 promonocytic cells. However, our results corroborate those of Tonon et al (2002), who showed activation of NF-B in monocyte-derived dendritic cells by a mutant form of pertussis toxin devoid of ADP-ribosylating activity.…”
Section: Discussionmentioning
confidence: 96%
“…1). Recent data have implicated B-oligomer moiety of the holotoxin, devoid of ADP ribosyltransferase activity, in regulating the activity of NF-B (Iordanskiy et al, 2002;Tonon et al, 2002). Therefore, we next determined whether B-oligomer activates NF-B in DDT 1 MF-2 cells.…”
Section: Pertussis Toxin Uncouples the A 1 Ar From Its G Protein(s)mentioning
confidence: 96%